Profession as Accounting for Non-Accounting Graduates - Putuhena, Hempry; Pattinaja, Elna M; Fauzan S, M Rifhki; Kilay, Trisye N (Journal of Financial and Behavioural Accounting, 2024)
The challenges of finding work are getting harder every day, and accounting graduates face intriguing issues as a result of the intense competition for available positions and remarkable problems. From the perspective of non-accounting graduates, this study provides a deeper analysis of the phenomenon that takes place in the accounting industry. Numerous industries that use non-accounting graduates as accountants frequently experience this situation. Eleven non-accounting graduates from various firms will be interviewed as part of a qualitative approach to address this situation. This study reveals that their lack of prior accounting knowledge stems from their varied educational backgrounds, such as; their motivation to stay in their current position comes from both internal and external sources; their lack of prior computer knowledge and proficiency is a barrier; and, finally, their adaptation process is facilitated by co-workers and independent self-education through educational materials or courses. It is hoped that as this research advances, both qualitative and quantitative methods will be used to help understand this phenomenon comprehensively.